2016
DOI: 10.3389/fpsyg.2016.01112
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Psychotherapeutic Micro-Interventions to Improve Mood in a Real-World Setting

Abstract: Background: Using mobile communication technology as new personalized approach to treat mental disorders or to more generally improve quality of life is highly promising. Knowledge about intervention components that target key psychopathological processes in terms of transdiagnostic psychotherapy approaches is urgently needed. We explored the use of smartphone-based micro-interventions based on psychotherapeutic techniques, guided by short video-clips, to elicit mood changes.Method: As part of a larger neurofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 106 publications
1
37
0
3
Order By: Relevance
“…Participants in all the studies summarised above (Kinderman et al, 2016;Meinlschmidt et al, 2016;Mohr et al, 2017;Roepke et al, 2015) were experiencing significant depression and/or anxiety symptoms, so it is unclear whether the MHapps would be effective for users experiencing subclinical symptoms. This has important implications for the recommendation of MHapps to different users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in all the studies summarised above (Kinderman et al, 2016;Meinlschmidt et al, 2016;Mohr et al, 2017;Roepke et al, 2015) were experiencing significant depression and/or anxiety symptoms, so it is unclear whether the MHapps would be effective for users experiencing subclinical symptoms. This has important implications for the recommendation of MHapps to different users.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative measurements of depression, anxiety, and mental wellbeing were also absent. Similarly, Meinlschmidt et al (2016) found that a MHapp that coached 27 male participants through CBT-based "micro-interventions" resulted in short-term mood improvements, but the long-term effects of the app were unclear. Mohr et al (2017) reported the efficacy of a suite of "IntelliCare" apps in significantly reducing depression, as measured by the 9-item Patient Health Questionnaire (PHQ-9), and anxiety, measured by the 7-item Generalised Anxiety Disorder scale (GAD-7).…”
mentioning
confidence: 99%
“…For either women, the times when she responds more slowly than her own average may reflect times when she reports more fatigue or depressed mood than her usual (within‐person differences). This information may facilitate the development of interventions to be directed to the right patients at the right time …”
Section: Introductionmentioning
confidence: 99%
“…This information may facilitate the development of interventions to be directed to the right patients at the right time. 10 Much of the previous research on CACD has examined factors that differ between persons such as treatment modality, 11 cognitive reserve, 12 symptomatology (eg, fatigue and depression), 13 In the current paper, we report on the results of an EMA study of cognitive performance in breast cancer patients. Participants completed three EMA cognitive tasks and rated their depressed mood and fatigue up to five times a day for a 2-week period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation